Transcytosis to Cross the Blood Brain Barrier, New Advancements and Challenges - Pulgar, Victor M. (Frontiers in Neuroscience, 2019)
The blood brain barrier (BBB) presents a formidable challenge to the delivery of drugs into the brain. Several strategies aim to overcome this obstacle and promote efficient and specific crossing through BBB of therapeutically relevant agents. One of those strategies uses the physiological process of receptor-mediated transcytosis (RMT) to transport cargo through the brain endothelial cells toward brain parenchyma. Recent developments in our understanding of intracellular trafficking and receptor binding as well as in protein engineering and nanotechnology have potentiated the opportunities for treatment of CNS diseases using RMT. In this mini-review, the current understanding of BBB structure is discussed, and recent findings exemplifying critical advances in RMT-mediated brain drug delivery are briefly presented.